VD_FINDINFO HC / 2013 / 740 vom 8. November 2013 - VD Tribunal cantonal (2013)
PROTECTION DE L'UNION CONJUGALE, PLACEMENT D'ENFANTS, EXPERTISE, RETRAIT DU DROIT DE GARDE, AUDITION DE L'ENFANT | 176 al. 3 CC, 297 al. 2 CC, 310 al. 1 CC, 314a al. 1 CC, 29 al. 2 Cst., 298 al. 1 CPC (CH)